HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TERHADAP PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK (KIA) DI UPT PUSKESMAS PANGKAJENE KABUPATEN SIDENRENG RAPPANG - Nurdin, Nasrayanti; Akib, Resky Devi; Setyawati, Eka Bella (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2026)
Introduction The Maternal and Child Health (KIA) Book is an important tool in supporting the safety of pregnant women and children through information and recording of health conditions. This study aims to determine the knowledge and attitudes of pregnant women towards the use of the KIA Book at the Pangkajene Health Center UPT, Sidenreng Rappang Regency in 2025. Method The study used a quantitative approach with a cross-sectional design, involving 70 pregnant women respondents selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using the Chi- Square Test. The results showed that most pregnant women had good knowledge (81.4%) and positive attitudes (95.7%) towards the use of the KIA Book. However, statistical analysis showed that there was no significant relationship between knowledge and utilization of the KIA Book ((p = 0.098), while there was a significant relationship between attitude and utilization of the KIA Book (p < 0.001). Conclution: These results indicate that the attitude of pregnant women has a greater influence on the utilization of the KIA Book than their level of knowledge. Therefore, intervention by health workers, especially midwives, in forming positive attitudes of pregnant women is important to increase the optimal use of the KIA Book. It is hoped that the results of this study can be used as evaluation material for health workers and further researchers in efforts to reduce maternal and infant mortality rates.